2008
DOI: 10.1016/j.visres.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Perceived speed differences explain apparent compression in slit viewing

Abstract: When a figure moves behind a stationary narrow slit, observers often report seeing the figure as an integrated whole, a phenomenon known as slit viewing or anorthoscopic perception. Interestingly, in slit viewing, the figure is perceived compressed along the axis of motion, e.g., a circle is perceived as an ellipse. Underestimation of the speed of the moving object was offered as an explanation for this apparent compression. We measured perceived speed and compression in anorthoscopic perception and found resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Thus, features presented at one retinotopic location are attributed to another one. These non-retinotopic attributions are not errors of the visual system but rather reflect systematic visual processing that maintains the identity of perceptual objects across space and time (Otto et al, 2009) and follows the rules of perceptual grouping (Aydin et al, 2008(Aydin et al, , 2009Öğmen et al, 2006;Otto et al, 2009). Similar non-retinotopic effects have been demonstrated for luminance (Shimozaki et al, 1999), color Watanabe and Nishida, 2007), shape Otto et al, 2006), size (Kawabe, 2008), and the conjunction of features (Cavanagh et al, 2008).…”
Section: Introductionmentioning
confidence: 58%
“…Thus, features presented at one retinotopic location are attributed to another one. These non-retinotopic attributions are not errors of the visual system but rather reflect systematic visual processing that maintains the identity of perceptual objects across space and time (Otto et al, 2009) and follows the rules of perceptual grouping (Aydin et al, 2008(Aydin et al, , 2009Öğmen et al, 2006;Otto et al, 2009). Similar non-retinotopic effects have been demonstrated for luminance (Shimozaki et al, 1999), color Watanabe and Nishida, 2007), shape Otto et al, 2006), size (Kawabe, 2008), and the conjunction of features (Cavanagh et al, 2008).…”
Section: Introductionmentioning
confidence: 58%
“…In a recent study (Aydın, Herzog, & Öğmen, 2008), we tested directly the speed underestimation hypothesis by measuring the perceived speed in anorthoscopic perception. Our results provided evidence against the speed underestimation hypothesis by showing that the perceived speed of the figure is always faster, not slower, than the physical speed.…”
Section: Introductionmentioning
confidence: 99%
“…The RFMF theory predicts that this apparent compression results from perceived speed differences between the different parts of the moving object. These predictions have also been tested formally, and the results lend further support to the RFMF theory (Aydın et al, 2008). Moreover, why and how attention is allocated to moving stimuli (Boi et al, 2009;Boi, Vergeer, Öğmen, & Herzog, 2011) and why masking is retinotopic but form perception can escape masking when a motion is predictable are other predictions of the RFMF theory that we have recently tested experimentally (Noory, Herzog, & Öğmen, in press), and we have demonstrated that RFMF can be implemented computationally to explain data at the quantitative level (Clarke et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…The RFMF theory offers a unified solution by constructing nonretinotopic representations according to motionbased reference frames. For instance, anorthoscopic perception (i.e., perceiving an object as a whole when it moves behind a narrow slit) had no viable explanation based on retinotopic theories, whereas it can readily be explained by the nonretinotopic representations of RFMF (see Öğmen, 2007), We recently tested this theory and showed how a motion-based reference frame can construct space and enable form perception (Agaoglu et al, 2012;Aydın et al, 2008Aydın et al, , 2009see also Nishida, 2004). Therefore, all of the theories employing center-surround antagonism that are listed above are tailored specifically for motion, whereas the RFMF theory accounts for all attributes of the stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation